(untitled) (MAUSAM, 1994)
The ave rage linkllBe method of cluster analys is was appl ied (or classifying the di stricts of Andhra Prad esh on th e b asis of monthly rainfall recorded. in diff ere nt sea so ns . The meth od of cluste ring h as the ad va nta ge of least subjectivity in clu ster formati on unlike th at of the pri nci pa l components method. Th e a nalysis was ca rried ou t seasonwise on th e basis of 30 ) ars of monthly rain fa ll data covering th e yea rs 1961-62 to 1 91. [I was found that the di stri cts ofAndh ra Prad esh ca n be classified iuto 5 10 7 d usters which depend on the seaso n. Ea st and Wesl God avari districts of coastal Andh ra region exh ib ited a similar pat tern in the rainfall of all the seasons: cert ain d istri cts c f Telangan a region also exh ibi ted a simila r pan crn in rai nfall of all th e seasons excepting the 5Ou th SI mensoon. In ce rtai n clu eters . there was 8 representetien u t’Ji.oJlril, ·u from all th e three ii ons of the Stale, Seesonwise clust erings a re also di scu ssed .